Where did good jobs go? Acemoglu and Marx on induced (skill replacing) technical change - Korkut A. Ertürk (The University of Utah, Department of Economics, 2019)
The paper lays out a hypothesis about the effect global oversupply of labor had on induced technological change, clarifying how it might have contributed to the demand reversal for high skill workers and other recent observed trends in technological change in the US. The argument considers the effect of market friendly political/institutional transformations of the 1980s on technology as they created a potential for an integrated global labor market. The innovations induced by the promise of this potential eventually culminated in the creation of global value chains and production networks. These required large set up costs and skill enhancing innovations, but once in place they reduced the dependence of expanding low skill employment around the globe on skill intensive inputs from advanced countries, giving rise to the wellobserved high skill demand reversal and sputtering of IT investment.
Keywords: F60; F15; O30; E10; B51; 330; income inequality; job polarization; skill downgrading; induced technological change; organization of work; craft economy; global production networks